IMPLEMENTASI FUNGSI-FUNGSI MANAJEMEN DALAM MENGELOLA PERPUSTAKAAN DI SMK NEGERI 2 SANGATTA UTARA - Adi Saputra, David; Ifendi, Mahfud; Utami, Ayu Febriyanti; Safitri, Nur; Maizah, St; Syah, Juhrika Wulan (MPI STAI Sangatta Kutai Timur, 2023)
This article focuses on implementing management functions in the Library of SMK Negeri 2 North Sangatta. This study aims to: (1) describe the implementation of management functions in library management at SMK Negeri 2 North Sangatta, (2) describe the constraints in implementing management functions at the library at SMK Negeri 2 North Sangatta. Based on the results of observations and direct interviews with librarians, it can be summarized as follows. First, the application management function, especially in processing library materials in the library at SMK Negeri 2 North Sangatta has not run optimally, starting from inventorying, classifying, and processing library materials. Second, there were obstacles faced by human resources (HR) or librarian personnel who are experts in the library, as well as limited books on majors such as the Department of heavy equipment engineering which were not yet available.